Leibniz’s twenty-four propositions - Leibniz, Gottfried Wilhelm; Betancourt, Alberto (Estudios de Filosofía, 1993)
It is reason that makes a thing exist in nature, instead of being nothing. This is the consequence of that great principle that nothing is done without reason and it is convenient to reason why one thing exists instead of any other.